Analisis Kinerja PT. Bank Pembangunan Daerah Sumatera Selatan Dan Bangka Belitung - Sugiri Dina (Jurnal Manajemen dan Bisnis, 2020)
The objectives of this research are to analyze the effect of BOPO towards Return On Asset (ROA) of Sumsel Babel Bank in the period of December 2012 – December 2014. This research used data from publication of quarterly financial reports and annual reports of Sumsel Babel Bank in the period of December 2014 – December 2016. Analysis technique in this research is simple linier regression for obtaining overall concept about the relationship between one variable with the other variables. The result of this research show that BOPO influence towards the performance of Sumsel Babel Bank proxied by ROA of 66.4% and the remaining 33.6% is influenced by other factors which is not examined in this research. The results of this research are expected to be used as suggestion, either for Sumsel babel bank to managing the company or for the investor to determine the investment strategy